2023
DOI: 10.1001/jamanetworkopen.2023.21554
|View full text |Cite
|
Sign up to set email alerts
|

Association of Serum Brain-Derived Tau With Clinical Outcome and Longitudinal Change in Patients With Severe Traumatic Brain Injury

Abstract: ImportanceBlood-based measurements of total tau (T-tau) are commonly used to examine neuronal injury in patients with traumatic brain injury (TBI), but current assays do not differentiate between brain-derived tau (BD-tau) and tau produced in peripheral tissues. A novel assay for BD-tau has recently been reported that selectively quantifies nonphosphorylated tau of central nervous system origin in blood samples.ObjectivesTo examine the association of serum BD-tau with clinical outcomes in patients with severe … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 17 publications
0
7
0
Order By: Relevance
“…19,20 Moreover, CSF surrogate markers of neurodegeneration, including proteins t-tau and 14-3-3, remain fundamental and widely used to support the diagnosis of CJD in patients with RPDs despite the recent introduction of the prion RT-QuIC, a specific CSF assay for the detection of PrP Sc . 20 Since plasma p-tau is strongly associated with amyloid pathology, 11,21 and plasma BD-tau with the intensity of neurodegeneration and cortical injury, 17,22 we hypothesized that the combined use of plasma BD-tau and p-tau181 may also provide valuable information in patients with RPD. Here, we have investigated the value of these novel tau-specific plasma biomarkers in the RPD diagnosis compared to established CSF markers.…”
Section: Discussionmentioning
confidence: 99%
“…19,20 Moreover, CSF surrogate markers of neurodegeneration, including proteins t-tau and 14-3-3, remain fundamental and widely used to support the diagnosis of CJD in patients with RPDs despite the recent introduction of the prion RT-QuIC, a specific CSF assay for the detection of PrP Sc . 20 Since plasma p-tau is strongly associated with amyloid pathology, 11,21 and plasma BD-tau with the intensity of neurodegeneration and cortical injury, 17,22 we hypothesized that the combined use of plasma BD-tau and p-tau181 may also provide valuable information in patients with RPD. Here, we have investigated the value of these novel tau-specific plasma biomarkers in the RPD diagnosis compared to established CSF markers.…”
Section: Discussionmentioning
confidence: 99%
“…This observation aligns with prior data on the delayed response of NfL to brain injury 13 and its earlier detection by BD-tau. 24 It remains speculative to assume that this difference might be rooted in the dynamic interaction of tau with microtubules 20,21 primarily in dendrites 40,41 as opposed to NfL’s more static role as a core filament in axons. 42 Notably, while axons start to fully degrade only 72 hours after injury, 23 dendrites are among the first structural components to retract and degrade upon ischemia.…”
Section: Discussionmentioning
confidence: 99%
“…18 Unlike NfL, which serves as a core structural protein within axons, 19 Tau dynamically binds to microtubules, mainly in dendrites and distal axons, 20,21 and may thus be released into the extracellular space more quickly upon neuronal death. 22,23 Indeed, in recent studies on neurodegenerative diseases 18 and traumatic brain injury 24 , BD-tau outperformed established biomarkers of brain injury including NfL in the early detection of CNS pathology.…”
Section: Introductionmentioning
confidence: 99%
“… 2 We found that plasma/serum BD-tau outperforms T-tau as a biomarker for Alzheimer disease–type neurodegeneration 2 and that increased BD-tau concentrations associated with unfavorable outcome after traumatic brain injury. 3 Based on these findings, we hypothesize that circulating acute-phase BD-tau concentrations are associated with functional outcome after ischemic stroke.…”
Section: Introductionmentioning
confidence: 88%